Aderência empresarial à Lei de Incentivo ao Esporte: vantagens e riscos sob a ótica dos principais atores - Barreto, Annina Patricia Imboden (2025)
Since its enactment, Law 11.438/2006, known as the Sports Incentive Law (Lei de Incentivo ao Esporte – LIE), has established itself as an important instrument for promoting sports in Brazil. Through the implementation of supported projects, thousands of individuals of various age groups have benefited. In addition to social impacts, the use of the LIE offers strategic advantages to sponsoring companies, such as increased brand visibility, enhanced corporate social responsibility, and improved institutional image, all without direct additional costs. However, adherence to the policy is restricted to companies taxed under the actual profit regime (lucro real), which, combined with other factors, has limited its reach. Data from the Brazilian Federal Revenue Service (RFB) and the Ministry of Human Rights and Citizenship (MDHC) indicate that, in 2015, less than 1.5% of eligible companies used the LIE to sponsor sports projects (Brasil, 2017; Brasil, 2019). Given this scenario, the general objective of this study is to identify the reasons why most companies under the actual profit regime do not sponsor sports projects through the LIE, considering the perspectives of the three main actors involved: the Federal Government, proposing organizations, sponsoring companies, and nonsponsoring companies. This descriptive research employed a qualitative approach through an exploratory field study. Semi-structured interviews were conducted with representatives of the four groups mentioned and analyzed using the content analysis technique proposed by Bardin (2010). The main findings include the influence of institutional strategy, the role of accounting in decision-making, and the importance of coordination between proponents and sponsors. The study also identified the need for greater project customization and improvements in institutional communication from the Federal Government. Based on these results, five strategies were proposed to improve the implementation and effectiveness of the LIE: (i) strengthening institutional communication; (ii) training accounting professionals; (iii) simplifying bureaucratic processes; (iv) enhancing the technical qualifications of proponents; and (v) customizing prospecting strategies to fit company profiles. These proposals offer practical insights for public and private managers and highlight the need for more coordinated and strategic engagement among the actors involved to expand the effectiveness of the LIE as a public policy for promoting sports and social development.